Assessment of Nevirapine Prophylactic and Therapeutic Dosing Regimens for Neonates. (15th August 2017) - Cressey, Tim R.; Punyawudho, Baralee; Le Coeur, Sophie; Jourdain, Gonzague; Saenjum, Chalermpong; Capparelli, Edmund V.; Jittayanun, Kanokwan; Phanomcheong, Siriluk; Luvira, Anita; Borkird, Thitiporn; Puangsombat, Achara; Aarons, Leon; et al.
Abstract : Background: Nevirapine (NVP) is a key component of antiretroviral prophylaxis and treatment for neonates. We evaluated current World Health Organization (WHO) weight-band NVP prophylactic dosing recommendations and investigated optimal therapeutic NVP dosing for neonates. Methods: The PHPT-5 study in Thailand assessed the efficacy of "Perinatal Antiretroviral Intensification" to prevent mother-to-child transmission of HIV in women with <8 weeks of antiretroviral treatment before delivery (NCT01511237). Infants received a 2-week course of zidovudine/lamivudine/NVP (NVP syrup/once daily: 2 mg/kg for 7 days; then 4 mg/kg for 7 days). Infant samples were assessed during the first 2 weeks of life. NVP population pharmacokinetics (PK) parameters were estimated using nonlinear mixed-effects models. Simulations were performed to estimate the probability of achieving target NVP trough concentrations for prophylaxis (>0.10 mg/L) and for therapeutic efficacy (>3.0 mg/L) using different infant dosing strategies. Results: Sixty infants (55% male) were included. At birth, median (range) weight was 2.9 (2.3–3.6) kg. NVP concentrations were best described by a 1-compartment PK model. Infant weight and postnatal age influenced NVP PK parameters. Based on simulations for a 3-kg infant, ≥92% would have an NVP trough >0.1 mg/L after 48 hours through 2 weeks using the PHPT-5 and WHO-dosing regimens. For NVP-based therapy, a 6-mg/kg twice daily dose produced a trough >3.0 mg/L in 87% of infants at 48 hours and 80% at 2 weeks. Conclusion: WHO weight-band prophylactic guidelines achieved target concentrations. Starting NVP 6 mg/kg twice daily from birth is expected to achieve therapeutic concentrations during the first 2 weeks of life.